2009
DOI: 10.1179/174328009x461050
|View full text |Cite
|
Sign up to set email alerts
|

Shock compression of reactive powder mixtures

Abstract: The shock-compression of reactive powder mixtures can yield varied chemical behaviour with occurrence of mechanochemical reactions in the time-scale of the high-pressure state, or thermochemical reactions in the time-scale of temperature equilibration, or simply the creation of densepacked highly reactive state of material. The principal challenge has been to understand the processes that distinguish between mechanochemical (shock-induced) and thermochemical (shock-assisted) reactions, which has broad implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 123 publications
(268 reference statements)
1
40
0
Order By: Relevance
“…The lack of a predictive understanding of these materials leads to their underutilization and therefore significant effort is being dedicated to characterizing and modeling these reactions. 1 Two distinct modes for reaction upon impact have been identified, shock-assisted and shock-induced chemical reactions. 6 Shock-assisted reactions occur in the period of thermal equilibration typically well after the shock wave has passed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of a predictive understanding of these materials leads to their underutilization and therefore significant effort is being dedicated to characterizing and modeling these reactions. 1 Two distinct modes for reaction upon impact have been identified, shock-assisted and shock-induced chemical reactions. 6 Shock-assisted reactions occur in the period of thermal equilibration typically well after the shock wave has passed.…”
mentioning
confidence: 99%
“…1,7 However, nanoscale reactive composites are significantly more sensitive to impact and thermal ignition and have faster reaction rates than mixtures using micron size powders due to higher surface areas and smaller diffusion distances. 2,8,9 It has also been observed that higher bulk densities can lower impact ignition thresholds in nano mixtures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The high exothermic energy release inherent in the reaction pathways of the Ti/B system in particular is postulated to promote combustion in Al powders by enhancing localization phenomena and mixing in powder compacts. The reactive behavior in these systems under shock loading or high strain rates depends largely on extrinsic properties such as microstructural distribution and constituent size/morphology, as well as intrinsic physical properties such as particle hardness and surface reactivity [1,2,3,4,5]. The crucial elements necessary for impact-induced reaction initiation in heterogeneous systems however remain unknown.…”
Section: Introductionmentioning
confidence: 99%